Nurses’ views on workplace wellbeing programmes - Wright, Nicola; Zakarian, Melissa; Blake, Holly (Mark Allen Healthcare, 2016)
Workplace stress is prevalent amongst nurses. Healthcare employers have implemented complementary and alternative therapies (CATs) for relaxation and stress management, within workplace wellbeing programmes for their employees. In-depth interviews were conducted with 12 registered nurses to explore the perceptions and experiences of nurses towards accessing CATs within and outside the workplace. Interviews were audio recorded and transcribed verbatim. Data were analysed using conventional, qualitative thematic techniques. Themes identified were “Perceptions of Complementary and Alternative Therapies for Stress Management” and “Engagement with Workplace Wellness Schemes”. CATs have a role within workplace wellbeing programmes and nurses are not averse to accessing them, although there are barriers to access that need to be addressed.